The PSS Quality Framework for Solar Home Systems. (August 2016) - Kebir, Noara Zohra; Philipp, Daniel
Abstract: In September 2015, the United Nations General Assembly has adopted the Sustainable Development Goals; they include SDG 7 targeting universal access to electricity by 2030. Reaching this goal implies huge investments in generation capacity, grid extension and densification. However, according to the International Energy Agency, 70% of the world's population currently excluded from electricity services can only be reached by decentralized solutions such as Mini Grids and Solar Home Systems. The use of Solar Home Systems (SHS) has shown mixed results in the last decades. In literature, 'quality' is often mentioned as an important success factor. However, the term 'quality' often stays undefined and actors have various understandings of it. The authors propose a framework for the definition of the quality of SHS with a focus on the economic benefit of the end-users and based on the concept of Product-Service Systems. In this approach, products and services are equal parameters. This enables a flexible design and dimensioning of SHS without implying a fixed set of international quality standards. Doing so, the PSS Quality Framework for SHS avoids creating preferences for products from industrialized nations and underlines the enormous potential of local manufacturing and services in developing countries, particularly in Sub-Saharan Africa.